The Management of Communication Skills Develoepment in Literature High Secondary Education from the Student’s Point of View - Ngoc Hung, Le; Yen, Duong Hoang; Huyen, Nguyen Phuong; Huong, Nguyen Thu; Oanh, Ho Thi (VNU Journal of Science: Education Research; Vol 38 No 2, 2022)
There are many theoretical and empirical studies on the development of communication skills in various target groups. However, there is the lack of research on the development of communication skills in literature high secondary education from the management sciences perspective. This paper applies the systems theory, social constructivism and management behavior approache to study the development of communication skills including literature reading, writing, listening, speaking and skills of communication with teachers, class-mates, family members and others as well as skills of using internet – connected mass media. The paper also use survey method to collect data from the non-random sample of students of a high secondary school in Hanoi in order to explore the school management behavior and the students’ the development of communication school in literature education. The research findings tend to recommend management measures such as the teachers’ active listening to students, the creating favorable opportunities for students to communicate and self – actualize in literature class and the assessment for the student’s progress in literature capacities and communication skills.